HUBUNGAN SIFAT KEPRIBADIAN GURU IPS TERHADAP MOTIVASI BELAJAR SISWA DALAM PROSES PEMBELAJARAN PADA MTs. NEGERI DI KOTA PALU - Rosmiati, Rosmiati (Katalogis, 2016)
The main problems of this research are: (1) Is there a significant relationship between personality character of Social Science Instruction teacher and student’s motivation in learning process? (2) How much the relationship between personality character of Social Science Instruction teacher and student’s motivation in learning process? The purposes of this research are: (1) to know and analyze the relation between personality character of Social Science Instruction teacher and student’s motivation in learning process and (2) to know and analyze the relationship between personality character of Social Science Instruction teacher and student’s motivation in learning process. This research is a descriptive correlation used with the purpose to describe the character ongoing at the time of the research and searching the causes from the indication with the data analysis technique to test the research hypothesis using correlation analysis of Pearson Product Moment (PPM). The result of this research showed that there is a significant relationship between personality character of Social Science Instruction teacher and student’s motivation in learning process. And then, the personality character of Social Science Instruction teacher have a strong enough relationship to student’s motivation, the correlation value of 0,486 and the determination coefficient amounting to 23,62 percent. The correlation value of 0,486 when referring to the theoretical interpretation of the correlation coefficient according to Ridwan (2002:228), have a value of r is between 0.40-0.599 with interpretation between the variables X and Y correlation is quite strong.